Characterization of LY2775240, a selective phosphodiesterase‐4 inhibitor, in nonclinical models and in healthy subjects. Issue 3 (13th February 2021) - Patel, Dipak R.; Urva, Shweta; Ho, Stephen; Buckman, Cody J.; Ma, Yanfei; Lim, Jean; Sissons, Sean E.; Zuniga, Mary S.; Philips, Diane; Cox, Karen; Dairaghi, Daniel J.
Abstract : Abstract: LY2775240 is a highly selective, potent and orally‐administered inhibitor of phosphodiesterase 4 (PDE4), and is being investigated as a treatment option for inflammatory disorders, such as psoriasis. LY2775240 was investigated in rodent and rhesus monkey nonclinical models. Treatment with LY2775240 led to significant reductions in TNFα production, a marker of PDE4 engagement upon immune activation, in both nonclinical models. In the first part of a 2‐part first‐in‐human randomized study, a wide dose range of LY2775240 was safely evaluated and found to be well‐tolerated with common adverse events (AEs) of nausea, diarrhea, and headache. No serious AEs were reported. The pharmacokinetic profile of LY2775240 was well‐characterized, with a half‐life that can support once‐a‐day dosing. An ex vivo pharmacodynamic (PD) assay demonstrated dose‐dependent PDE4 target engagement as assessed by reduction in TNFα production. A 20 mg dose of LY2775240 led to near‐maximal TNFα inhibition in this PD assay in the first part of the study and was selected for comparison with the clinical dose of apremilast (30 mg) in the crossover, second part of this study. The 20 mg dose of LY2775240 demonstrated sustained maximal (50%–80%) inhibition of TNFα over all timepoints over the 24‐h duration. The comparator apremilast achieved peak inhibition of ~ 50% at only 4 h postdose with a return to about 10% inhibition within 12 h of dosing. In summary, the nonclinical data and safety, tolerability, and PK/PD data in healthy subjects supports further investigation of LY2775240 in inflammatory indications. Study Highlights WHAT IS THE CURRENT KNOWLEDGE ON THE TOPIC? Phosphodiesterase 4 (PDE4) inhibitors, such as apremilast, are currently approved to treat autoimmune disorders, such as psoriasis. LY2775240 is an oral PDE4 inhibitor being developed for treatment of a variety of inflammatory disorders. The degree of enzymatic inhibition achieved by PDE4 inhibitors clinically is poorly understood. WHAT QUESTION DID THIS STUDY ADDRESS? This study investigated single ascending doses of LY2775240, a highly selective oral PDE4 inhibitor, in healthy subjects. LY2775240 was well‐tolerated over the dose range evaluated, and pharmacokinetic/pharmacodynamic (PD) profiles were well‐characterized. WHAT DOES THIS STUDY ADD TO OUR KNOWLEDGE? This study evaluated different doses of LY2775240 and subsequently compared a selected LY2775240 dose with the clinical dose of apremilast with an ex vivo assay. This information builds a connection between target engagement and clinical efficacy. HOW MIGHT THIS CHANGE CLINICAL PHARMACOLOGY OR TRANSLATIONAL SCIENCE? This is the first report of an ex vivo PD assay that has been systematically implemented in a PDE4 inhibitor Phase 1 study. Early investigation of exposure‐response relationships versus a comparator can support evaluation of clinically meaningful doses of investigational agents.